Production Performance, Meat Quality and Economic Appraisal of Broiler Rearing with Tamarind Leaves (Journal of the Bangladesh Agricultural University, 2020)
The study was carried out to investigate the effects of Tamarind tree leaves with dry and fermentation using beneficial bacteria on growth performance, carcass characteristics, meat oxidative stability and economics of broiler rearing. A total of 90 day-old Ross-308 unsexed broiler chicks were assigned to three dietary treatments consisting of three replications having 10 birds in each for 4 weeks in a completely randomized design. Dietary treatments were, T0 = Control (basal diet), T1 (basal diet + 0.4% dried Tamarind tree leaves on DM basis) and T2 (basal diet + 0.4% fermented Tamarind leaves on DM basis). According to the results, overall average daily gain (ADG) were increased and feed conversion ratio (FCR) improved in both T1 and T2 groups compared to the control group (P